Management of cubitus varus deformity by three-dimensional osteotomy: analysis of outcome - Khan, M. Zahidul Haq; Das, Krishna Priya; Islam, M. Ashraful; Sarker, M. Hafijur Rahman; Sidny, Nabil Zunayed (International Journal of Research in Orthopaedics, 2024)
Background: Cubitus varus deformity, commonly resulting from malunited supracondylar fractures of the humerus, is prevalent in pediatric and adolescent populations. Traditional treatment methods often fall short in addressing the complex three-dimensional nature of this deformity. This study aims to evaluate the efficacy and outcomes of three-dimensional osteotomy in correcting cubitus varus deformity. Methods: This prospective interventional study was conducted at the Department of Orthopaedic Surgery, BSMMU, Shahbag, Dhaka, from March 2016 to September 2018. A total of 40 patients aged 8 to 20 years with cubitus varus deformity were enrolled. Participants underwent three-dimensional osteotomy, and outcomes were assessed using the Mayo Elbow Performance Score (MEPS) and functional recovery parameters. Results: The majority of patients (75%) achieved bone union within 8-10 weeks post-osteotomy. The MEPS results were promising, with 40% of patients scoring 'Excellent' and 45% scoring 'Good'. Functional outcomes were predominantly positive, with 95% of patients reporting satisfactory results. The complication rate was low, with 80% of patients experiencing no postoperative complications. Conclusions: Three-dimensional osteotomy is an effective and reliable surgical intervention for treating cubitus varus deformity, offering high rates of patient satisfaction, minimal complications, and improved functional outcomes. This technique presents a promising option for orthopedic surgeons in managing this complex deformity.